Bridging higher education and industrial needs - Sarjit Singh, Manvender Kaur; Rathakrishnan, Mohan; Md Ali, Rohaya (2019)
In an intercultural setting, it is timely to say that there is a crucial need to bridge the dimensions of professional discourses such as the engineering discourses, the business discourses and the legislative discourses. While various approaches are used to investigate intercultural communication, genre analysts believe that the use of specialist informants is beneficial, to provide important information on the targeted discourse community. This paper reports one such possibility to extract reliable information related to the needs of the written communication. Data was extracted using a set of interview questions manoeuvred based on Munby’s CNP model. The findings highlighted the extent of workplace intercultural communication involving particularly the English language written skill.